Characterization of a New Cold-Adapted and Salt-Activated Polysaccharide Lyase Family 7 Alginate Lyase from Pseudoalteromonas sp. SM0524 - Chen, Xiu-Lan; Dong, Sheng; Xu, Fei; Dong, Fang; Li, Ping-Yi; Zhang, Xi-Ying; Zhou, Bai-Cheng; Zhang, Yu-Zhong; Xie, Bin-Bin (Frontiers in Microbiology, 2016)
Marine bacterial alginate lyases play a role in marine alginate degradation and carbon cycling. Although a large number of alginate lyases have been characterized, reports on alginate lyases with special characteristics are still rather less. Here, a gene alyPM encoding an alginate lyase of polysaccharide lyase family 7 (PL7) was cloned from marine Pseudoalteromonas sp. SM0524 and expressed in Escherichia coli. AlyPM shows 41% sequence identity to characterized alginate lyases, indicating that AlyPM is a new PL7 enzyme. The optimal pH for AlyPM activity was 8.5. AlyPM showed the highest activity at 30oC and remained 19% of the highest activity at 5oC. AlyPM was unstable at temperatures above 30oC and had a low Tm of 37oC. These data indicate that AlyPM is a cold-adapted enzyme. Moreover, AlyPM is a salt-activated enzyme. AlyPM activity in 0.5-1.2 M NaCl was 6-fold higher than that in 0 M NaCl, probably caused by a significant increase in substrate affinity, because the Km of AlyPM in 0.5 M NaCl decreased more than 20 folds than that in 0 M NaCl. AlyPM preferably degraded polymannuronate and mainly released dimers and trimers. These data indicate that AlyPM is a novel PL7 endo-alginate lyase with special characteristics.